ANALISIS BIAYA DAN WAKTU PEKERJAAN PELAT LANTAI BETON KONVENSIONAL DAN FIBER BOARD PADA BANGUNAN BAJA - Susila, Herman; Sungkono, Kukuh Kurniawan Dwi (Journal of Civil Engineering and Infrastructure Technology, 2025)
The development of construction technology continues to experience very rapid progress. This is indicated by the many types of modern materials and equipment in the construction sector. Building construction projects have various problems in the planning and implementation stages. Construction costs are the main factor in the planning and implementation stages, while in the implementation of construction work, time and cost are the main factors. The success and failure of a construction job are greatly influenced by cost and time. This study will conduct a cost and time analysis study of conventional floor slabs and Kalsi Floor 20 on steel structure buildings. The stages of the study are: The first stage: conducting an analysis of the modeling of a 3-story building structure using conventional concrete slabs and Kalsi Floor slabs. The analysis is carried out with steel structure building planning standards. The second stage: conducting cost estimates and scheduling of a 3-story building with conventional concrete slabs and Kalsi Floor slabs. The third stage: conducting an analysis of the costs and schedules of conventional concrete slab buildings and Kalsi Floor slabs. The results of this study are that steel structure work using Kalsi Floor 20 floor slabs is more economical by Rp. Rp. 212,722,091.86. The implementation time for steel structure work using Kalsi Floor floor slabs is 27 days faster